Prevalence and determinants of undernutrition among under-five children in Bangladesh using nationally representative data - Nahar, Mst. Arifun; Mondal, Md. Nazrul Islam; Haque, Moynul; Parvin, Shela; Sultana, Mst. Sharmin; Islam, Md. Rasel; Chowdhury, Mohammad Rocky Khan (Paediatrica Indonesiana, 2025)
Background Malnutrition manifests as undernutrition and overnutrition, with stunting, underweight, and wasting being critical forms of undernutrition that hinder the physical and cognitive development of children under five in Bangladesh. Objective To assess the nutritional status of under five children and identify key determinants of undernutrition. Methods This study utilized data from the 2019 Multiple Indicator Cluster Survey (MICS), including 22,448 children under five. Nutritional status was assessed in terms of three indicators: stunting, wasting, and underweight. The analysis focused on sociodemographic factors. Both bivariate and multivariable binary logistic regression models were used to analyze the data. The bivariate analysis examined the individual relationship between each independent variable and the outcome, while the multivariable model simultaneously included all relevant predictors to identify factors independently associated with the outcome after controlling for potential confounders. Results The prevalence of multiple forms of undernutrition was 3.2%, and the overall prevalence of at least one form of undernutrition was 36.5%, with stunting affecting 27.9% of children, underweight 22.6%, and wasting 9.8%. Among districts, stunting was most prevalent in Sunamganj (45.9%), underweight in Habiganj (37.9%), and wasting in Lakshmipur (15.9%). Children from the poorest households had significantly higher odds of experiencing stunting (aOR 2.2; 95% CI 1.92 to 2.51; p<0.001), underweight (aOR 2.4; 95%CI 2.04 to 2.73; P<0.001), and wasting (aOR 1.5; 95% CI 1.24 to 1.83; P<0.001) compared to those from the richest households. Additionally, children in families with a history of child mortality had increased odds of stunting (aOR 1.2; 95% CI 1.05 to 1.32; P<0.01), underweight (aOR 1.2; 95% CI 1.07 to 1.36; P<0.01), and wasting (aOR 1.2; 95% CI 1.06 to 1.45; P<0.01). Conclusion Household wealth and a history of child mortality were key determinants of undernutrition among children under five. Parental education, particularly the lack of primary education in both parents, was strongly associated with stunting and overall undernutrition. These findings highlight the need to improve socioeconomic conditions and promote parental education to reduce childhood undernutrition in Bangladesh.